2023
DOI: 10.1021/acs.est.2c09587
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pretreatments and Anaerobic Digestion Shape the Virome and Functional Microbiome in Fecal Sludge

Abstract: The decomposition and pathogen inactivation of fecal sludge (FS) are vitally important for safely managing onsite sanitation and protecting public and environmental health. However, the microbiome and virome assemblages in FS after chemical and biological treatments remain unclear. Here, we reported the differences in the solid reduction and microbiomes of FS subjected to potassium ferrate (PF), alkali (ALK), and sodium hypochlorite (NaClO) pretreatments and anaerobic digestion (AD). The PF and NaClO pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Viral metagenomic sequencing is a rising technique recovering bioinformation on viruses from environmental samples. There have been some studies on lab-scale AD reactors revealing the characteristics of viral community in AD habitat, but the report of the diversity and dominant species of viruses in a full-scale AD plant through long-term monitoring is still lacking. , The virus identification thresholds used in the AD studies were divergent, making the results less comparable and reliable. Some methods concerning the host linkages of phages have indicated that the combination of viral and prokaryotic metagenomic data could provide more reliable results but have not been applied in the AD process. , The current research status is calling for consistent experimental procedures and full-scale reports of AD virome studies.…”
Section: Introductionmentioning
confidence: 99%
“…Viral metagenomic sequencing is a rising technique recovering bioinformation on viruses from environmental samples. There have been some studies on lab-scale AD reactors revealing the characteristics of viral community in AD habitat, but the report of the diversity and dominant species of viruses in a full-scale AD plant through long-term monitoring is still lacking. , The virus identification thresholds used in the AD studies were divergent, making the results less comparable and reliable. Some methods concerning the host linkages of phages have indicated that the combination of viral and prokaryotic metagenomic data could provide more reliable results but have not been applied in the AD process. , The current research status is calling for consistent experimental procedures and full-scale reports of AD virome studies.…”
Section: Introductionmentioning
confidence: 99%